PEMBATALAN PUTUSAN PAILIT PENGADILAN NIAGA OLEH MAHKAMAH AGUNG - Brenda Sundah (Jurnal Education and Development, 2022)
Bankruptcy is general confiscation of all assets of the Bankrupt Debtor whose management and settlement is carried out by the Curator under the supervision of the Supervisory Judge as stipulated in the Law. Bankruptcy occurs because of the debtor's inability to perform its obligations in terms of debt repayment, for this reason the creditor submits an application for bankruptcy to the debtor. This research is aimed to find out about the cancellation of the bankruptcy decision of the commercial court by the Supreme Court because it does not meet the requirements of simple proof. The research method used is the normative juridical method, namely the approach to legislation, concepts and case studies of the Supreme Court's decision. The results of this study can be concluded that, the cancellation of the bankruptcy decision of the commercial court by the constitutional court because the judge has made a mistake in applying the law, in this case the bankruptcy proof requirements are not fulfilled in the bankruptcy petition by the creditor.